Integrative Taxonomy Clarifies the Historical Flaws in the Systematics and Distributions of Two Osteobrama Fishes (Cypriniformes: Cyprinidae) in India - Boni Amin Laskar; Dhriti Banerjee; Sangdeok Chung; Hyun-Woo Kim; Ah Ran Kim; Shantanu Kundu (Fishes, 2024)
The taxonomy and geographical distributions of Osteobrama species have historically posed challenges to ichthyologists, leading to uncertainties regarding their native ranges. While traditional taxonomy has proven valuable in classification, the utility of an integrated approach is restricted for this particular group due to limitations in combining information from biogeography, morphology, and genetic data. This study addresses the taxonomic puzzle arising from the recent identification of Osteobrama tikarpadaensis in the Mahanadi and Godavari Rivers, casting doubt on the actual distribution and systematics of both O. tikarpadaensis and Osteobrama vigorsii. The research reveals distinctions among specimens resembling O. vigorsii from the Krishna and Godavari riverine systems. Notably, specimens identified as O. vigorsii from the Indian Museum exhibit two pairs of barbels, while those from the Godavari River in this study are identified as O. tikarpadaensis. Inter-species genetic divergence and maximum likelihood phylogeny provide clear delineation between O. vigorsii and O. tikarpadaensis. The study suggests that O. vigorsii may be limited to the Krishna River system in southern India, while O. tikarpadaensis could potentially extend from the Mahanadi River in central India to the Godavari River in southern India. Proposed revision to morphological features for both species, accompanied by revised taxonomic keys, aim to facilitate accurate differentiation among Osteobrama congeners. The data generated by this research provide a resource for future systematic investigations into cyprinids in India and surrounding regions. Further, the genetic diversity information obtained from various riverine systems for Osteobrama species will be instrumental in guiding aquaculture practices and formulating effective conservation action plans.